Case Report: A novel method of needle-free transseptal puncture - Lee, Chia-Chen; Chao, Chen-An; Chang, Su-Huan; Chen, Chun-Kai; Chen, Yen-Siou; Lin, Chang-En; Jeng, Tsung-Ping; Yu, Chih-Chieh (Frontiers in Cardiovascular Medicine, 2024)
BackgroundIn the era of fluoroless catheter ablation (CA), achieving a successful transseptal puncture (TSP) presents a significant challenge. We introduce a novel technique for zero-fluoroscopy and cost-effective needle-free TSP.Case summaryWe describe two cases where a GMS-1 guidewire (0.025 inch, pigtail configuration; Toray Medical Co., Ltd., Japan) was utilized for TSP. This technique was performed using either fluoroscopy or intracardiac echocardiography (ICE). The procedure was completed successfully in both cases, with no complications reported.ConclusionThe use of a 0.025 inch GMS-1 guidewire with an electrocautery technique enables effective transseptal puncture without the need for a needle or fluoroscopy. This novel approach offers a safe, efficient, and zero-fluoroscopic alternative for TSP.